4
$\begingroup$

The equation to solve is: $$(x^3y^3+x^2y^2+xy+1)ydx+(x^3y^3-x^2y^2-xy+1)xdy=0$$

I tried putting $xy=t$ but that just gave me this: $$\frac{t^3-t^2-t+1}{t^3+t^2+t+1}dt=\frac{dx}{x}$$

I suppose there must be some clever factoring involved somewhere but I can't see it so can someone guide me on how to advance or perhaps suggest an alternate method?

$\endgroup$
  • 6
    $\begingroup$ $\frac{t^3-t^2-t+1}{t^3+t^2+t+1}=\frac{(t+1)(t-1)^2}{(t+1)(t^2+1)}=1-\frac{2t}{t^2+1}$. $\endgroup$ – Feng Shao Sep 6 '19 at 4:54
2
$\begingroup$

The given equation is of the form $f_1(xy)ydx+f_2(xy)xdy=0.$ Here, $M=(x^3y^3+x^2y^2+xy+1)y$ & $N=(x^3y^3-x^2y^2-xy+1)x$ $$\therefore I.F.=\frac1{Mx-Ny}\\ =\frac1{2x^2y^2(xy+1)}$$ $\text{Multiplying the I.F. with the equation, we get}$ \begin{align}\\ &{\begin{aligned}\\ \frac{(x^3y^3+x^2y^2+xy+1)y}{2x^2y^2(xy+1)}dx &+\frac{(x^3y^3-x^2y^2-xy+1)x}{2x^2y^2(xy+1)}dy=0 \end{aligned}}\\ &{\begin{aligned}\\ \implies\frac{(x^2y^2+1)(xy+1)}{x^2y(xy+1)}dx &+\frac{(x^2y^2-1)(xy-1)}{xy^2(xy+1)}dy=0 \end{aligned}}\\ &{\begin{aligned}\\ \implies\frac{x^2y^2+1}{x^2y}dx &+\frac{(x^2y^2-1)(xy-1)}{xy^2(xy+1)}dy=0 \end{aligned}}\\ &{\begin{aligned}\\ \implies ydx+\frac{dx}{x^2y}+&\frac{(x^2y^2-1)(xy-1)}{xy^2(xy+1)}dy=0 \end{aligned}}\\ \end{align} $\therefore\text{the solution is}$ \begin{align} &{\begin{aligned}\\ \int_{(\text{y const})}Mdx+ &\int(\text{terms of N not containing x}) dy=c \end{aligned}}\\ &{\implies \int ydx+\int\frac{dx}{x^2y}=c}\\ &{\implies xy-\frac{1}{xy}=c}\\ \end{align}

| cite | improve this answer | |
$\endgroup$
2
$\begingroup$

Grouping terms, we get

$$(x^3y^3+1)(ydx+xdy) - (x^2y^2+xy)(xdy-ydx) = 0$$

Now substitute $t=xy$ and $s=\frac{y}{x}$

$$\implies dt = ydx+xdy \hspace{20 pt} x^2 ds = \frac{t}{s}ds = xdy - ydx$$

turning the differential equation into

$$s(t^3+1)dt - t^2(t+1)ds = 0$$

which is now separable and yields

$$\int \frac{ds}{s} = \int \frac{t^3+1}{t^2(t+1)}dt = \int 1 - \frac{1}{t} + \frac{1}{t^2}dt$$

$$\implies \log|s| = t - \log|t| - \frac{1}{t} + C$$

Substituting back in for $x$ and $y$

$$\log (y^2) - xy + \frac{1}{xy} = C$$

or rearranging terms we can have

$$y^2\exp\left(\frac{1}{xy} - xy \right) = C > 0$$

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.